2007
DOI: 10.1179/174328007x160236
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of n-diamond

Abstract: Allotropes of carbon based materials, such as graphite, fullerenes and nanotubes, and diamond are currently a focus of great interest. New diamond (n-diamond) has been proposed as a new carbon allotrope; its electron diffraction pattern matches that of cubic (Fd3 m) diamond apart from some additional reflections that are forbidden for diamond, indexed as {200}, {222} and {420}. n-Diamond has been found experimentally for more than 10 years, yet its structure and stability are not unambiguously resolved, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 86 publications
(235 reference statements)
3
36
0
Order By: Relevance
“…Crystal morphologies vary from angular to rounded and from monocrystalline to twinned, and ND diameters average 3-4 nm (range: 1 nm-2.9 mm), with most measuring between 1 and 20 nm, a typical size for detonation-formed NDs (Wen et al 2007). The quantification method discussed above was used to estimate abundances of NDs and revealed concentrations in carbon spherules of 10-3680 ppb (mean: 755 ppb) and in bulk sediment of 11-494 ppb (mean: 200 ppb).…”
Section: Abundance and Stratigraphic Distribution Of Ndsmentioning
confidence: 99%
See 4 more Smart Citations
“…Crystal morphologies vary from angular to rounded and from monocrystalline to twinned, and ND diameters average 3-4 nm (range: 1 nm-2.9 mm), with most measuring between 1 and 20 nm, a typical size for detonation-formed NDs (Wen et al 2007). The quantification method discussed above was used to estimate abundances of NDs and revealed concentrations in carbon spherules of 10-3680 ppb (mean: 755 ppb) and in bulk sediment of 11-494 ppb (mean: 200 ppb).…”
Section: Abundance and Stratigraphic Distribution Of Ndsmentioning
confidence: 99%
“…Hough et al (1997) suggested that the K-Pg NDs formed by the CVD process, which requires a source of carbon vapor and the reducing atmosphere of the fireball (Wen et al 2007). For the K-Pg, it is proposed that the NDs formed when the impactor collided with carbon-rich Yucatan bedrock, e.g., limestones and dolostones containing hydrocarbons (Belcher et al 2005).…”
Section: Potential Origin From Volcanism or In The Mantlementioning
confidence: 99%
See 3 more Smart Citations